Kant and fine art: An essay on Kant and the philosophy of fine art and culture - Kemal, Salim (Oxford Clarendon Press, 1986)
Integrating Kant's ideas on aesthetics and morality, Dr. Kemal explains how Kant's theories emphasize that art is critical to the development of culture and community goals. He clarifies Kant's often obscure efforts to justify artistic judgements and demonstrates Kant's claim that they have their own necessity. Containing explanations of many difficult terms present in Kant's Critique of Judgment, this study is a valuable guide to understanding Kant's association of beauty and morality